(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
Over time, accounting is becoming an important ally for managers, supplying the decision-making process with information. In addition, of course, to assisting in the internal and external control of accounting facts. This paper presents a survey that seeks to verify the industrial cost methods used in the company ABC, familiarizing with tools and/or suggesting new ones. The research was carried out with a visit to the company, in which its industrial processes were observed. Then, general analyses of the entire production process of the industry were carried out and, from the data obtained, it was concluded that the raw material stock system has flaws and can be optimized so as to not compromise the performance of activities that affect the level of service provided to customers. Furthermore, note the need of the company to define what will really be its production focus, whether in the machines division, in the foundry or even in both.